Pendidikan ANALISIS STRATEGI PENDIDIK TERHADAP PENGEMBANGAN KARAKTER SISWA DI ERA DIGITAL - Nasution, Hafiz; Abdul Fattah Nasution; Ryan Fazli Zulna; Rahmad Riadi Batubara (Cemara Education and Science, 2024)
Character education is an effort to instill religious, ethical and moral values ​​in students through science, with the help of parents, teachers and the community. This is very important for the formation and development of students' personalities. All children are born with extraordinary potential. However, to exploit this potential, they need proper learning and socialization. Each child's personality will be formed and develop optimally. In this digital era, children have easy access to digital media. This digital era, which has positive and negative influences, is the responsibility of teachers, parents and instructors. Therefore, it is the duty of teachers, parents and the adult community to monitor and control children's use of digital media